2021
DOI: 10.1038/s41467-021-22143-x
|View full text |Cite
|
Sign up to set email alerts
|

An ALYREF-MYCN coactivator complex drives neuroblastoma tumorigenesis through effects on USP3 and MYCN stability

Abstract: To achieve the very high oncoprotein levels required to drive the malignant state cancer cells utilise the ubiquitin proteasome system to upregulate transcription factor levels. Here our analyses identify ALYREF, expressed from the most common genetic copy number variation in neuroblastoma, chromosome 17q21-ter gain as a key regulator of MYCN protein turnover. We show strong co-operativity between ALYREF and MYCN from transgenic models of neuroblastoma in vitro and in vivo. The two proteins form a nuclear coac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 72 publications
0
33
0
Order By: Relevance
“…The known role of ALYREF as a regulator of DNA binding guided further analyses that uncovered ALYREF-MYCN interaction in a nuclear coactivator complex which stimulates transcription of the 'ubiquitin specific peptidase 3 (USP3), consequently reducing MYCN ubiquitination and degradation. This finding therefore opens novel opportunities for targeting this deubiquitinase activity through the development of USP3 inhibitors [68].…”
Section: Alyrefmentioning
confidence: 89%
See 1 more Smart Citation
“…The known role of ALYREF as a regulator of DNA binding guided further analyses that uncovered ALYREF-MYCN interaction in a nuclear coactivator complex which stimulates transcription of the 'ubiquitin specific peptidase 3 (USP3), consequently reducing MYCN ubiquitination and degradation. This finding therefore opens novel opportunities for targeting this deubiquitinase activity through the development of USP3 inhibitors [68].…”
Section: Alyrefmentioning
confidence: 89%
“…The Marshall team used a bioinformatic approach to identify critical genes on 17q in high-risk NBs by evaluating frequency of gains distal to 17q21.31 using whole genome sequencing data from NB tumors from the US TARGET database [68]. A total of 1044 transcripts from the 17q21-ter locus were analyzed for differential gene expression in 17q21-tergain patients (1) and MYCN-amplified patients (2) in the same cohort.…”
Section: Alyrefmentioning
confidence: 99%
“…We further explored the detailed interactions and regulatory mechanisms between USP3 and COL9A3 or COL6A5. As a DUB, USP3 has been identified to have deubiquitination effects on its wide targets within cellular entities and during cell activities in various malignancies [ 10 , 11 , 27 , 28 ]. Das et al have shown that USP3 can upregulate the expression of Cdc25A through its DUB activity, which promotes cell cycle progression and tumorigenesis [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased NME1 gene expression has also been associated with high-risk NB, suggesting a potential role of histidine kinase signalling in tumour pathogenesis [ 25 ]. Moreover, ALYREF gene has been proposed as a codriver factor for oncogenesis in NB by in vitro and in vivo transgenic models, co-operating with N-Myc for USP3 transcription upregulation, and thus regulating MYCN turnover [ 26 ]. However, a better definition of these genes’ involvement is still to be determined.…”
Section: Genetic Predisposition and Chromosome Instability In Nbmentioning
confidence: 99%